ANALISI YURIDIS HILANGNYA STATUS HAK GUNA BANGUNAN AKIBAT DITERLANTARKAN PEMILIKNYA - Sianipar, Ronia; Bhakti, Rizki Tri Anugrah (LPPM Universitas Putera Batam, 2020)
Humans live and live on the land and use the land to carry out their lives. Once the importance of land for human life, animals, and plants because it can produce natural resources that are very useful for many people, then in need of a regulation that regulates land. In Indonesia the regulations concerning land and buildings thereon are regulated in the UUD RI 1945 (Constitution of the Republic of Indonesia) article 33 paragraph 3, Undang-Undang Nomor 5 Tahun 1960 concerning Basic Regulations on Agrarian Principles, Government Regulation Number 40 of 1996 concerning Business Use Rights, Building Use Rights and Rights Use of Land, Government Regulation Number 11 of 2010 concerning Control and Utilization of Abandoned Land. Researchers analyze abandoned land in terms of Government Regulation No. 11 of 2010 concerning Control and Utilization of Abandoned Land and rules regarding legal protection for loss of building rights. The method used in this research is normative, where researchers obtain data from a literature study which will then be tested with legal principles. The results of the study show that although the Government of Indonesia has issued a number of rules regarding land rights, in its implementation many problems related to these rights are still found, such as the unilateral loss of land rights by the government. A deeper study and renewal of the law relating to the regulation of neglected land is needed so that the community and agencies or government relating to land control have a common understanding so that problems do not occur when land policing is neglected in the future.